A revision of the genus Leptotyphlops in northeastern Africa and southwestern Arabia (Serpentes: Leptotyphlopidae) - Broadley, Donald G.; Wallach, Van (Zootaxa, 2007)
The species of Leptotyphlops in northeastern Africa and southwestern Arabia (i.e. between 18°N and 12°S and between 29°E and 52°E) are revised. Twenty-five species belonging to five species groups are recognised, the taxonomy being based largely on skull morphology and visceral anatomy. Seven new species (L. ionidesi, L. tanae, L. howelli, L. mbanjensis, L. keniensis, L. aethiopicus and L. nigroterminus) and one new subspecies (L. scutifrons pitmani) are described. Wallach & Lanza (2004) have revived Leptotyphlops braccianii (Scortecci) from the synonymy of L. macrorhynchus (Jan & Sordelli), with Glauconia variabilis Scortecci regarded as a synonym. They also revived L. erythraeus (Scortecci) from the synonymy of L. macrorhynchus and L. yemenicus Scortecci from the synonymy of L. nursii. Leptotyphlops monticolus (Chabanaud) is now revived from the synonymy of L. emini (Boulenger). Glauconia latirostris Sternfeld is reinstated as a full species. Leptotyphlops nursii (Boulenger), long known from the Arabian peninsula, is recorded from higher altitudes in northern Somalia. Descriptions of the visceral anatomy are presented for all species found in eastern and southern Africa. A key based on external characters is provided, the known variation in meristic and visceral characters is tabulated and the distributions mapped.